INTEGRASI PENDIDIKAN MULTIKULTURAL DAN PENDIDIKAN INKLUSI DALAM SISTEM PENDIDIKAN ISLAM - Helmiati; Nur Ikhlas; Hariza Hasyim (JURNAL KAJIAN ISLAM MODERN, 2026)
Multicultural and inclusive education are strategic approaches to developing an Islamic education system that is just, democratic, and human-centered. Multicultural education emphasizes appreciation for cultural, ethnic, and religious diversity, while inclusive education ensures equal learning opportunities for all students, including those with special needs. This study employs a library research approach to analyze the characteristics, implementation, and implications of integrating these two approaches for the advancement of Islamic education in Indonesia. The findings indicate that multicultural education is democratic, humanistic, and respects differences, whereas inclusive education is adaptive, collaborative, and non-discriminatory. Integration can be implemented through curriculum integration, teacher training, development of an inclusive school culture, and community collaboration. This article highlights the limited empirical studies on the integration of these approaches in madrasahs and pesantrens and proposes an integrative framework that can serve as a reference for inclusive Islamic education policies in Indonesia. Keywords: multicultural education, inclusive education, Islamic education, social justice